DAKWAH DAN PEMAHAMAN ISLAM DI RANAH MULTIKULTURAL - Imam Amrusi Jailani (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2014)
Development of Islam in Indonesia or in the local domain did not show the same performance as in his homeland, namely in the Arab lands. This is due to the acculturation the values of Islam and the local culture. Variabilities in Islamic appearance is also showed the variabilities in understanding on Islam. Applying variable approaches on Islam, textual-contextual and functional-structural, will show the varieties of Islam too: normative Islam, factual Islam, ideal Islam or universal Islam, and Local Islam. From this illustrates that in reality, we are often confronted with the face of normative Islam, Islamic factual, ideal or universal Islam and the local Muslim. The study found the patterns of understanding and attitude of inclusive-exclusive, with all the effects that will be caused, either constructive or destructive, supporting or undermined the development of Islam. Based on the finding, it is needed a concept and strategy of da‘wa which is really effective and approved by multi-culture society like Indonesia.